2013
DOI: 10.1891/0047-2220.44.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Employment and College Attendance Outcomes for Youth in Transition: Implications for Policy and Practice

Abstract: An analysis of vocational rehabilitation (VR) data over a period of five years from a Midwestern state was conducted to identify predictors of employment and college attendance outcomes for youth with disabilities receiving transition services. The database included 26,292 transition cases. Transition outcomes were identified for 4,010 youth (15.3%). Results indicated that 11.2% of the cases were closed from application (ineligible), 45.2% were closed before the rehabilitation plan was completed, and 13.1% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Except for the graduation rate, the outcomes of the participating students were relatively modest (e.g., 37% participated in paid internships, 35% got jobs, and 13% enrolled in college classes). However, these results are encouraging when comparing them with our analysis of the state VR agency’s data that indicate that over a period of 5 years, 58.3% of the students who were accepted for VR services through the transition preparation program did not complete their rehabilitation goals and only 9.2% had competitive or supported employment to reach successful VR closures (Balcazar, Oberoi, & Keel, 2013). It should be noted that prior to this intervention, none of the students with disabilities in this charter school had opportunities to participate in paid internships or vocational trainings and the charter school was never invited to participate in the VR transition preparation program.…”
Section: Discussionmentioning
confidence: 69%
“…Except for the graduation rate, the outcomes of the participating students were relatively modest (e.g., 37% participated in paid internships, 35% got jobs, and 13% enrolled in college classes). However, these results are encouraging when comparing them with our analysis of the state VR agency’s data that indicate that over a period of 5 years, 58.3% of the students who were accepted for VR services through the transition preparation program did not complete their rehabilitation goals and only 9.2% had competitive or supported employment to reach successful VR closures (Balcazar, Oberoi, & Keel, 2013). It should be noted that prior to this intervention, none of the students with disabilities in this charter school had opportunities to participate in paid internships or vocational trainings and the charter school was never invited to participate in the VR transition preparation program.…”
Section: Discussionmentioning
confidence: 69%
“…Most importantly, according to the analysis, spending between $5,000 and $8,000 per consumer is associated with the maximum rate of rehabilitation (a 1,360% higher likelihood of getting rehabilitated). Balcazar et al (2013) also found that the chances of a youth in transition gaining competitive employment increased as the amount of money spent by the VR counselor on the case increased. Furthermore, youth who received vocational guidance and on-the job supports had higher chances of obtaining competitive employment than of going to college.…”
Section: Vr Services For African American With Mental Health Diagnosesmentioning
confidence: 85%
“…In another study, Balcazar, Oberoi, and Keel (2013) examined a VR database from a Midwestern state that included 26,292 transition cases. Transition outcomes were identified for 4,010 youth (15.3%) and analyzed based on factors of gender, race, and disability type.…”
Section: Vr Services For African American With Mental Health Diagnosesmentioning
confidence: 99%